Analisis Akuntansi Biaya Lingkungan Industri Kimia Di Kota Cilegon Sebagai Wujud Implementasi dari Green Accounting - Mohamad Husni; Mochamad Fahru Komarudin; Riyanthi Idayu (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2024)
The main focus of industry players now is the environment, where industry players are required to be more responsible for the environment as a result of their operating activities which incidentally intersect with the use of the environment, because one of the biggest contributions related to environmental problems is the fruit of industrial activities produced by companies such as waste or something else. This study aims to find out how much the application of green accounting and environmental cost analysis begins with identification, recognition, measurement, presentation and disclosure in the chemical industry company PT Nippon Shokubai Indonesia, this research is a qualitative research in the form of a case study. The results of the study stated that PT Nippon Shokubai Indonesia, had implemented Green Accounting accounting practices even though it was not what was expected, environmental management carried out by PT Nippon Shokubai Indonesia by processing waste was carried out by themselves using the Increator tool and if waste production was excessive the Company appointed a third party licensed in waste processing, especially for B3 waste, regarding reporting aspects PT Nippon Shokubai Indonesia has expense items related to social and environmental activities, but specifically reporting related to environmental costs has not been reported.